Something Drew Me In': The Professional and Personal Impact of Working with Spirituality in Addiction Recovery - Cleary, Daniel (Religions, 2018)
This research addresses the impact of working with spirituality from the perspective of the addiction worker with five separate interviews conducted with people who have been working in the area of addiction for ten years or more. Interview transcripts were analysed using qualitative thematic analysis. Three themes emerged, the findings of which indicate that there is an impact on the addiction worker when spirituality is part of the recovery process. The themes that emerged are (A) Being Constructive (B) Productivity and (C) Managing Therapeutic Ruptures. The findings pose important implications for training and supervision of people involved in addiction work in that there needs to be an openness and awareness around spirituality whether the worker believes in it or not. The findings show that when spirituality is part of the recovery process, it enables the addiction worker to deal with and manage all issues that arise with the person with the addiction, as well as enhancing the work and life of the worker. Most striking across the five participant's transcripts was their ability to engage in the difficult work of addiction along with the opportunity that the participants have for personal and professional growth in their work and in their own spiritual life.